(untitled) (Revista LIDER, 2020)
Achieving a sustainable rural development that is respectful with the environment, culture and traditions of the local agents, has lead the public administrations and private industries to support parallel and complementary activities besides the traditional ones in rural areas. This work presents the results obtained in an econometric study carried out along the second trimester of 2006 in order to estimate the quantitative demand of wine tourism in a given geographical area: the Montilla-Moriles Designation of Origin in the province of Cordoba, and to know the characteristics of these tourists in order to be able to establish the measures required to enhance that touristy route so as to increase the wealth of the area.